D Mitochondrial DNA Damage can Promote Atherosclerosis Independently of Reactive Oxygen Species and Correlates with Higher Risk Plaques in Humans. (31st May 2014) - Yu, Emma
Abstract : Introduction: Mitochondrial DNA (mtDNA) damage occurs in both the vessel wall and in circulating cells in human atherosclerosis. However, whether mtDNA damage promotes atherogenesis or is a consequence of tissue damage is unknown. We assessed the hypothesis that mtDNA damage is present, and can directly promote atherosclerosis and affect plaque composition. Methods: To assess whether mtDNA damage may contribute to atherogenesis we examined apolipoprotein E null mice (ApoE -/- ). We characterised the development of atherosclerotic plaques, and concomitantly assessed for mtDNA damage and mitochondrial dysfunction. We then studied ApoE -/- mice, also deficient for mtDNA polymerase γ proof reading activity (polG -/- /ApoE -/- ), to determine whether mtDNA defects directly promote atherosclerosis. The mice were assessed for levels of atherosclerosis, mtDNA damage and mitochondrial respiratory function. We characterised phenotypic changes in vascular smooth muscle cells (VSMCs) and monocytes. We also examined the association between mtDNA damage and human disease. We used qPCR to quantify the levels of mtDNA damage in human plaques and normal aortic samples. Furthermore, we examined whether leukocyte mtDNA damage correlates with atherosclerosis extent, or plaque vulnerability. Results: MtDNA damage occurred early in the vessel wall in ApoE -/- mice, before significant atherosclerosis developed. MtDNA defects were also identified in circulating monocytes and liver, and were associated with reduced respiratory complex activity. PolG -/- /ApoE -/- mice showed extensive mtDNA damage, impaired mitochondrial respiration and increased atherosclerosis in the absence of increased ROS. PolG -/- /ApoE -/- VSMCs had decreased oxygen consumption rate, and ATP content was reduced despite an increased in basal glycolysis. The bioenergetic impairment was associated with altered VSMC phenotype, with reduced proliferation and increased apoptosis. Furthermore polG -/- /ApoE -/- monocytes showed increased inflammatory cytokine release, and transplantation with polG -/- /ApoE -/- bone marrow induced plaque vulnerability. Consistent with these findings, leukocyte mtDNA damage in humans was associated with thin cap fibroatheromas- the lesions with the highest risk of cardiovascular events on subsequent follow up. Conclusions: MtDNA defects promote atherosclerosis and plaque vulnerability, independently of ROS, through effects on VSMCs and monocytes. MtDNA damage is therefore not only causative, but also indicates higher risk in atherosclerosis. Protection against mtDNA damage, and improvement of mitochondrial function, are potential areas for new therapeutics.